Trainer Basics - Piskurich, George (Association for Talent Development, 2003)
Subject matter experts (SMEs) and occasional trainers are increasingly sharing the training burden in organizations. Yet these "instant trainers" often are not familiar with even the basic terminology or practices of the training profession. Trainer Basics is written specifically to answer three key questions these new trainers ask: What does a trainer do and why? How can I develop must-have skills quickly? How do I apply training knowledge today? New trainers will appreciate the informative quick learning "hits" hroughout the book, including helpful reminders called Think About This, cut-to-the-chase rules called Basic Rules, and additional key concept points called Noted. Every chapter ends with quick learning exercises called Getting It Done to reinforce key chapter information. Written in direct and understandable language by a veteran trainer, this book also offers professional trainers a much-needed tool to help train these new ranks of trainers. Just hand Training Basics to a new trainer and within a few hours the job of explaining the basics of instructional design, adult learning, needs analysis, evaluation, and presentation and facilitation skills is done.